Synthesis, Mechanical, and Tribological Performance Analysis of Stir-Casted AA7079: ZrO2 + Si3N4 Hybrid Composites by Taguchi Route - G. Jegan; P. Kavipriya; T. Sathish; S. Dinesh Kumar; T. Samraj Lawrence; T. Vino (Advances in Materials Science and Engineering)
Currently, the aluminum alloys are utilized more in level of all industries for different applications; furthermore, industries need high-strength alloys for making innovative components. For those reasons, many researchers hope to prepare hybrid aluminum metal matrix composites at various composition levels. In this experimental work, we intended to prepare the hybrid metal matrix composites such as aluminum alloy 7079 with reinforcement of ZrO2 + Si3N4 through stir-casting process. Major findings of this work, as to optimize the stir-casting process, can be to continually conduct wear test and evaluate the microhardness of the stir-casted specimens. Optimization of stir-casting process parameters is a preliminary work for this research by Taguchi tool. The chosen parameters are % of reinforcement (0%, 4%, 8%, and 12%), agitation speed (450 rpm, 500 rpm, 550 rpm, and 600 rpm), agitation time (15 min, 20 min. 25 min, and 30 min), and molten temperature (700°C, 750°C, 800°C, and 850°C). The prepared stir-casted materials are tested by wear analysis and microhardness analysis, through Pin-on-Disc wear tester and Vickers hardness tester, respectively. Wear parameters are optimized, the minimum wear rate is evaluated, and also the wear worn-out surfaces are examined through SEM analysis.